PUSTAKA DIGITAL BERBASIS APLIKASI SEBAGAI UPAYA PELESTARIAN MUSIK KERONCONG - Pratama, Annisa Kusuma; Welly Suryandoko; Setyo Yanuartuti; Joko Winarko; Martadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by structural gaps in the preservation and accessibility of keroncong music, particularly the lack of systematic digital documentation and the declining awareness among younger generations. The study aims to develop and validate a web-based digital library system (Croeng.id) that enhances information retrievability, user engagement, and cultural understanding. The method employed is Research and Development (R&D) using a modified 3D model (Define, Design, Develop), implemented through iterative development and continuous validation. Data were collected through alpha testing (internal evaluation) and beta testing involving experts and general users. System evaluation refers to ISO 9241-11:2018 standards, focusing on three key indicators: effectiveness, efficiency, and user satisfaction. Quantitative analysis shows a feasibility level of 88.0%, exceeding the ≥80% threshold, indicating that the system is highly feasible. Qualitative findings further reveal improvements in accessibility, speed of information retrieval, and depth of understanding of keroncong music. These results confirm that a culture-based digital system functions not only as a repository but also as an interactive learning medium. Therefore, this development represents a strategic cultural intervention contributing to sustainable preservation and the strengthening of music education in the digital era.